IDENTIFIKASI WISATA KULINER DI PULAU BANGKA - Levyda Levyda; Giyatmi Giyatmi; Kania Ratnasari (Fakultas Pariwisata Universitas Pancasila, 2020)
This study aims to identify culinary tourism on Bangka Island. The method used is content analysis the Bangka Island tour packages available on the travel agency website. Furthermore, the field was confirmed by participatory observation and interviews of restaurant owners, gift shops, and agro-tourism in Pangkal Pinang, Sungai Liat, and Belinyu. Culinary tours offered by travel agents are to enjoy local food at local restaurants, enjoy the agro-tourism experience in the Bangka Botanical Garden,learn about making crackers, and shopping in Kampung Gedong, and shopping for souvenirs. The tourist attraction in the restaurant is local food and atmosphere. In the Bangka Botanical Garden agrotourism area, it offers a learning experience of various organic fruits and vegetables, farms, and sales of cow's milk and dairy products. Gedong Village offers cultural and culinary tourism, in the form of making crackers that are mostly done by residents. Although it has not been explicitly stated, as a culinary tourism activity, many travel agents offer culinary tourism experiences on Bangka Island.